Analysis of Loyal Work Behavior Personality Perspective and Organizational Work Culture - Nindia, Zahra Ayu (AKADEMIK: Jurnal Mahasiswa Ekonomi & Bisnis, 2023)
Seeing loyal, professional and total work behavior is a blessing in itself for an organization. Because having employees who are dedicated and committed to work and the company can bring progress and provide long-term benefits, both material and psychological. Work behavior beyond standards is more skewed by ingrained personality and culture. So it is interesting to study, to see how big the impact is on company performance. To prove this statement, a quantitative method was established with the implementation of a survey. Data were collected by distributing questionnaires and analyzed using probability-based linear regression statistics. The research subjects were employees of Perkebunan Nusantara 11 who were office employees. Sampling was carried out using the proportional method for each work unit, and the number of respondents was 70 people. The results of the study explain that the birth of work behavior beyond standards is more influenced by self-commitment or a personality that has been attached to an employee. In addition, the work model that has become a culture is a factor that shapes it. This suggests the importance of recruiting employees by looking at personality as capital in the formation of expected work behavior.